Phytoestrogens and sterols in waters with cyanobacterial blooms - Analytical methods and estrogenic potencies - Procházková, Tereza; Sychrová, Eliška; Javůrková, Barbora; Večerková, Jaroslava; Kohoutek, Jiří; Lepšová-Skácelová, Olga; Bláha, Luděk; Hilscherová, Klára (Chemosphere, 2017)
Compounds with estrogenic potencies and their adverse effects in surface waters have received much attention. Both anthropogenic and natural compounds contribute to overall estrogenic activity in freshwaters. Recently, estrogenic potencies were also found to be associated with cyanobacteria and their blooms in surface waters. The present study developed and compared the solid phase extraction and LC-MS/MS analytical approaches for determination of phytoestrogens (8 flavonoids - biochanin A, coumestrol, daidzein, equol, formononetin, genistein, naringenin, apigenin - and 5 sterols - ergosterol, β-sitosterol, stigmasterol, campesterol, brassicasterol) and cholesterol in water. The method was used for analyses of samples collected in stagnant water bodies dominated by different cyanobacterial species. Concentrations of individual flavonoids ranged from below the limit of detection to 3.58 ng/L. Sterols were present in higher amounts up to 2.25 μg/L. Biological potencies of these phytoestrogens in vitro were characterized using the hERα-HeLa-9903 cell line. The relative estrogenic potencies (compared to model estrogen - 17β-estradiol) of flavonoids ranged from 2.25E-05 to 1.26E-03 with coumestrol being the most potent. None of the sterols elicited estrogenic response in the used bioassay. Estrogenic activity was detected in collected field water samples (maximum effect corresponding to 2.07 ng/L of 17β-estradiol equivalents, transcriptional assay). At maximum phytoestrogens accounted for only 1.56 pg/L of 17β-estradiol equivalents, contributing maximally 8.5% of the total estrogenicity of the water samples. Other compounds therefore, most likely of anthropogenic origin such as steroid estrogens, are probably the major drivers of total estrogenic effects in these surface waters.
Keywords: steroly; Water; estron; Cholesterol; Isoflavones; estrogeny; lidé; tandemová hmotnostní spektrometrie; Estrogenicity; cholestadienoly; cholesterol; HeLa Cells; Estradiol; chemické látky znečišťující vodu; voda; Reservoir; Sterols; Cyanobacteria; Water Pollutants, Chemical; sitosteroly; Tandem Mass Spectrometry; fytoestrogeny; Humans; estradiol; Estrone; Fresh Water; Relative estrogenic potency; Phytosterols; sladká voda; Sitosterols; Sterol; Estrogens; genistein; HeLa buňky; fytosteroly; Cholestadienols; Receptors, Estrogen; Flavonoid; isoflavony; receptory pro estrogeny; Genistein; Phytoestrogens; sinice